TO INCREASE THE INTEREST OF YOUNGER STUDENTS IN SPORTS CIRCLES THROUGH THE FORMATION OF SPIRITUAL MORAL VALUES (American Journal of Pedagogical and Educational Research, 2024)
This article covers information on the growth and development of the body of Primary School students, physical rehabilitation of children, rehabilitation-oriented autoreflex special physical exercises,the formation of spiritual moral values, increased physical activity, yoga poses and control exercises, the formation of the correct figure.